Benign Breast Disorders –a Histiopathological Study in Tikrit City - Ghani, Nadia Adnan (Diyala Journal of Medicine, 2019)
Background: The objective of the present study is to determine the frequencies of various benign breast diseases (BBD) in female patient in Tikrit city. Aim: A retrospective descriptive study of all female patients visiting surgical clinic with breast problems was performed. This study was conducted at Tikrit Teaching Hospital and the main private histopathological laboratory in Tikrit over the period from January -2000 to the end of December 2007. All the patients were diagnosed as carcinoma were excluded. A total of 485 patients were included in this study. Results: About 35.7% (173/485) patients were belonged to the 3rd decade of life (age between 21-30 year), followed by 30.5% (148/485) were belong to 4th decade (age between: 31-40 years). Fibrocystic disease was the commonest of all benign breast disease, seen in about 33% (162/485) mainly in the 3rd, 4th &5th decades of life with peak at 31-40 years followed by fibroadenoma that is seen in 27.6%(134/485) of the cases mostly in the 2nd & 3rd decades of life. Conclusion: It is found that benign breast diseases are common problem in females of reproductive age.